Pengaruh Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan Bidang Lattas Pada Dinas Tenaga Kerja Kota Surabaya - Maqbula Arochman; Emilda Damayanti (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2022)
Resources is to evaluate the performance of employees in an organization. Leadership will affect the organization’s success rate in optimizing all available resources to realize organizational goals. In addition, motivation is also necessary for achieving employee performance because it has an impact on individuals to involve themselves in work that leads to achieving goals. This study analyses the influence of leadership and works motivation on employee performance. The population in this study were Lattas employees at the Surabaya City Labor Office, which consisted of 38 people, 31 assistants and seven administrative staff. The sampling analysis technique data used the census technique so that the sample studied was the entire population with 38 people. The analysis technique used in this study used multiple linear regression, while the t-test was the method to test the hypothesis. The results showed that leadership has a significant effect on employee performance and work motivation also concerned on employee performance.